Populism as a Visual Communication Style : An Exploratory Study of Populist Image Usage of Flemish Block/ Interest in Belgium (1991-2018) - Straetemans, Kevin (Politics of the Low Countries, 2025)
This article analyses the visual communication of the Flemish populist right-wing party Vlaams Blok/Vlaams Belang, and investigates whether or not the party uses a specific populist communication style in its campaign posters, whether or not its visual style evolves over time and how the party distinguishes itself from other (right-wing) parties in its use of images. To do this, the image use will be compared with the CVP/CD&V and the Volksunie/N-VA. This use of images will be investigated by analysing election posters from 1991 to 2018. The analysis shows that there is indeed a ‘populist visual style’. These items consist mainly of (negative) metaphors, false dilemmas, caricatures and the use of so-called ‘agonic’ visual techniques.